Managing Intellectual Capital in Public Hospital: Effects on Financial Performance - Anggun B.U.S. Depari; Budi Waluyo (Universitas Negeri Semarang, 2022)
This study examines effect of intellectual capital on the financial performance of public hospitals in Indonesia. The effect is proxied through Value Added Intellectual Coefficient (VAIC™), consisting of Value-Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). In addition, this study identifies differences in the influence on general and special hospitals. This study analyses the audited financial statements of 20 public hospitals with random effects approach. The results showed that VACA and STVA positively affected financial performance. In contrast, VAHU negatively affected the financial performance of all public hospitals. Although general and special hospitals have several different business models, the effect of intellectual capital on the financial performance is similar. This study provides theoretical implication to the rising stream of literature on intellectual capital in public service agencies, especially public hospitals. Public hospitals are expected to develop human capital to create added value for the organization by employing their flexibility in human resource management.